Managers' mobility, trade performance, and wages - Giordano Mion; Luca David Opromolla (European Central Bank (ECB), 2013)
Knowledge is key to the success of a firm. Firms and their managers acquire knowledge via channels which are often difficult to track down and quantify. By matching employer-employee data with trade data at the firm level we show that the export experience acquired by managers in previous firms leads their current firm towards higher export performance, and commands a sizeable wage premium for the manager. Export knowledge is decisive when it is market-specific: managers with experience related to markets served by their current firm receive an even higher wage premium; firms are more likely to enter markets where their managers have experience; exporters are more likely to stay in those markets, and their sales are on average higher. Our findings are robust to controlling for endogeneity. The impact of managers' export experience on a firm's export performance is at least as strong as that of firm productivity.
Keywords: M2; L2; F16; J31; J62; 330; export experience; firm trade performance; job mobility; managers; wage premium